“O saber que tem força de fontes”: por psicologias que acessem territórios plurais de existências - LIMA, Mayla de Aguiar (2022)
This work aims to present a critical reading on how the discourse of modernity, as a civilizing project, affects both individual and collective subjective formation. Thus, I propose that, through the decolonial perspective, it is possible to understand that the colonization process crossed the domains of territorial exploitation and the submission of peoples, reaching the modes of existence of the being and, consequently, shaping them. An articulation was made between the concepts of modernity/coloniality, emphasizing the coloniality of being to analyze how Psychology can expand into Psychologies that understand diversities of existences that were historically erased by colonial violence. With this, the general objective is to investigate how the option of “Latin American” colonial(s), based on the concept of coloniality, can contribute to a project of decolonization of Psychology, notably in studies on subjectivity. The methodological procedure excels in developing not only a theoretical and qualitative analysis from a bibliographic research, but also seeks to enable another look at what has been explained over the centuries on certain concepts involving the theme. For this purpose, “Latin American” colonial theorists were used, as well as authors from the field of Psychology. In this way, it is analyzed that, even though geographic colonialism has come to an end, colonial powers continue to be strongly rooted in our daily lives, reflexes that link past-present and act directly on our experiences. This study also attempts to propose a quick reflection around the issues of ethnic racial identities in Brazil and how these are linked to a plurality of experiences, narratives and re-existences that can be understood from the notions of coloniality presented, mainly with regard to the construction of being.